Hematological and immunological effects of gallium, indium, and arsenic in light emitting diodes manufacturing workers - Liao, Yen-Hsiung (International Journal of Medicine, 2015)
Purpose: To determine whether hematological and immunological changes occur in manufacturing workers in association with gallium, indium, and arsenic biomarkers in light-emitting diodes.Methods: 91exposed light-emitting diodes, workers and 24 referents were monitored for whole blood and urine levels of gallium, indium, and arsenic. Venous blood was also collected for routine and immunological analyses.Results: The mean levels of blood in, urine Ga, urine as, and mean corpuscular hemoglobin concentration (MCHC) in the exposed workers were significantly than in referents. The values of mean corpuscular volume (MCV), white blood cell counts (WBCs), neutrophils, lymphocytes, interferon-Î³ (IFN-Î³), and IgG in the exposed workers were lower than in referents. Combined exposure to Ga, In, and As showed a significant change in trends of decreased MCV, WBCs, neutrophils, lymphocytes, IFN,Î³, and IgG value, after adjusting for appropriate confounders.Conclusion: These findings indicated that heavier exposed to Ga, In, and As may suppress hematological and immunological variables.